Portable Wireless Item Identification System (PWIIS) / Mohammad Farid Saaid, Megat Syahirul Amin Megat Ali and Mohd Zikrul Hakim Noor - Saaid, Mohammad Farid; Megat Ali, Megat Syahirul Amin; Noor, Mohd Zikrul Hakim (Research Innovation Business Unit, 2014)
This project aims to create a technology that can help blind people in their daily lives. Usually, a person who is blind would not be able to identify the item in front of them. They need to touch, taste and smell each of the items they take to identify. As a result the process of identifying items will be slow as well as time consuming. In line with the increasing number of the blind people in Malaysia, related projects regarding blind people assistive should be built. Based on the problem statement, the creation of a technology-based device will help them to identify each item, thus the process will be quick and effective. Based on the study conducted, the use of RFID is the most suitable technology that can be used as a device for identifying items. Radio-frequency identification (RFID) is one of the wireless radio wave technologies which constantly transmits and receive signals using antennas if the tag is within the range of the detector. This device has been equipped with a microphone to record information about the items by using their voices and a speaker as a sender of information to the blind people. In addition, this device is portable and small. Hence it’s easy to carry. Furthermore, the study includes an analysis to find the specification of PWIIS. This analysis covered the study of PWIIS in term of performance, response and accuracy in order to test its capabilities. In summary, this device is able to help and assist the blind to identify the items in their daily lives. It is able to give them accurate and quick information compared to the conventional method. The novelty of this project is it is able to support larger size memory card to save data; use voice as the medium for recording and explain information; rechargeable battery; smaller and light size. PWIIS requires two main components which are PWIIS reader and the tag. The users simply need to affix adhesive RFID tag on each of the items they want. RFID reader will detect and catch each tag that has been affixed if they are in range of the detector. Next, they just need to record their voice based on the item information. Each of the detected signals will be processed by the microcontroller and play back the user’s voice that has been recorded as feedback through the speakers. Commercial Potential:- Portable Wireless Items Identification System (PWIIS) is a compact wireless technology tool which can help the user (blind people) in efforts to accelerate identification of objects. This device can assist and facilitate the user to identify a stock that has been sealed in the box or other storage compartment. PWIIS equipped with built-in audio system so that users can record information using their voice through a microphone and speaker. The recordable voice that contains the items’ information can be saved on an additional memory card.Research book: abstract only